Porting open source E-learning software to mobile platform - Tanveer, Jameal; Sultan, Md. Al-Mubin (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2010.